Knowledge and Practices towards Acne Vulgaris among Acne patients in a tertiary care hospital, Dina Nath, Pakistan - Zahida Perveen, Madiha Zulfiqar, Almas Raza, Shaista Umbreen, Zartaj Liaqat, Mariyam Saeed, N. Humayun Sheikh, S. Z. H. Naqvi, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the incidence, knowledge and practices in patients with acne vulgaris. Study design: Observational (Cross sectional) Place and duration of study: Department of Dermatology, Pak Red Crescent Teaching Hospital, Dina Nath, Kasurfrom 1st Aug, 2021 to 31st Jan 2022. Methodology: A total of 121 patients fulfilling the inclusion criteria were included in the study, written informed consent was taken on spot and responses were recorded on a pre-formed questionnaire. Data was then entered and analyzed using SPSS version 21 software and a P value of < 0.05 was considered statistically significant. Results: Out of 121 patients, 85(71%) were females and 35(29%) were males. 55(45%) patients had good knowledge and 66(55%) patients had poor knowledge. Among those having poor knowledge, 57% belong to 12-20 age group, 57% belong to female gender and 75% having poor knowledge were illiterate with a P-value of 0.02 which is statistically significant.Major source of information was family and friends in 65(54%) patients, followed by internet in 28(23%)patients.78% related acne with burning in epigastrium. 40% participants were in favor of using traditional medicine and 28% consulted specialist in 1 year Conclusion: Results of this study conclude that people with Acne in this part of Punjab have very poor knowledge regarding different aspects of Acne and its management. This leads to malpractice and poor management of Acne and is causing harm to the patient’s wellbeing. Educationalprograms and community-based health awareness programs should be arranged to impart knowledge and to remove the misconceptions regarding the Acne and its management. Keywords: Acne Vulgaris, Propionibacterium Acnes, Knowledge, Practices.